Bioretention cells remove microplastics from urban stormwater. (1st March 2021) - Smyth, Kelsey; Drake, Jennifer; Li, Yourong; Rochman, Chelsea; Van Seters, Tim; Passeport, Elodie
Highlights: Microplastics were quantified and characterized in stormwater and bioretention cell. More than 80% decrease in microparticles throughout the bioretention cell. Atmospheric deposition was the dominant source in urban runoff. Antecedent dry days and rainfall intensity correlate with microplastic counts. Abstract: Microplastic pathways in the environment must be better understood to help select appropriate mitigation strategies. In this 2-year long field study, microplastics were characterized and quantified in urban stormwater runoff and through a bioretention cell, a type of low impact development infrastructure. Concentrations of microparticles ranged from below the detection limit to 704 microparticles/L and the dominant morphology found were fibers. High rainfall intensity and longer antecedent dry days resulted in larger microparticle concentrations. In addition, atmospheric deposition was a source of microplastics to urban runoff. Overall, these results demonstrate that urban stormwater runoff is a concentrated source of microplastics whose concentrations depend on specific climate variables. The bioretention cell showed an 84% decrease in median microparticle concentration in the 106–5, 000 µm range, and thus is effective in filtering out microplastics and preventing their spread to downstream environments. Altogether, these results highlight the large contribution of urban stormwater runoff to microplastic contamination in larger aquatic systems and demonstrate the potential for current infiltration-based low impact development practices to limit the spread of microplastic contamination downstream. Graphical abstract: Image, graphical abstract